2021
DOI: 10.3390/biology10050404
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Fear Extinction Memory and Resistance to Age-Related Cognitive Decline in Butyrylcholinesterase Knockout Mice and (R)-Bambuterol Treated Mice

Abstract: Butyrylcholinesterase (BChE) is detected in plaques preferentially in Alzheimer’s disease (AD) and may be associated with stress disorders. However, the physiological function of BChE in the central nervous system remains to be further investigated. BChE knockout (KO) mice and wild-type (WT) mice with orally or intranasal administration of (R)-bambuterol were used to explore the effect of BChE on behavior changes. (R)-bambuterol is a specific and reversible inhibitor of BChE. The behavior changes were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…Altered cognitive functions were associated with normal nicotinic receptor function, though the muscarinic receptor function was altered in the knockout model. Preliminary studies on the effect of (R)-bambuterol, a specific and reversible inhibitor of BChE, suggested that it may be used in the treatment of early cognitive decline[ 79 ].…”
Section: Significance Of Studying Butyrylcholinesterase Variantsmentioning
confidence: 99%
“…Altered cognitive functions were associated with normal nicotinic receptor function, though the muscarinic receptor function was altered in the knockout model. Preliminary studies on the effect of (R)-bambuterol, a specific and reversible inhibitor of BChE, suggested that it may be used in the treatment of early cognitive decline[ 79 ].…”
Section: Significance Of Studying Butyrylcholinesterase Variantsmentioning
confidence: 99%
“…Advanced techniques like DESI and MALDI-MS imaging have detected significant changes in lipid metabolites, such as phosphatidylethanolamines, phosphatidylcholines, and glycerophospholipids, in early-stage AD mouse models [111]. These techniques have also been instrumental in observing the distribution of specific lipids like DHA in dementia mouse models [75] and studying the enzymatic activity of biomarkers like BChE in AD patients [112]. Lipid molecules, including lysophospholipids such as LPC and LPG, accumulate in Aβ plaques, affecting cell membrane functions like ion transportation [113] and signal reception [113].…”
Section: Application Of Spatial Metabolomics In the Study Of Admentioning
confidence: 99%
“… 12 Pesticides like carbofuran are employed in the cultivation of maize, rice, and cotton crops. 13 FDA-approved carbamate-containing drug molecules, such as ( R )-bambuterol, have the potential to be used in the treatment of cognitive decline and post-traumatic stress disorder (PTSD), 14 while pyridostigmine is commonly used to treat myasthenia gravis. 15 On the other hand, rivastigmine acts as an acetylcholinesterase (AChE) inhibitor.…”
Section: Introductionmentioning
confidence: 99%